2001
DOI: 10.1038/sj.ejcn.1601176
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid status of women of reproductive age

Abstract: Objective: Healthy foetal and infant development is dependent on an adequate maternal supply of essential and polyunsaturated fatty acids (PUFA). While there are published data on the fatty acid status of pregnant women, there are few on the status of non-pregnant women of reproductive age. The aims of this study were to test the hypotheses that the fatty acid status of non-pregnant women is affected by socio-economic status and anthropometric, behavioural and obstetric factors. Design: Observational study Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…By 28 weeks, DHA accounted for a significantly higher % TFA in RBC (p < 0.05) and a higher concentration in both RBC and plasma (p < 0.05) in the fish oil compared with placebo group. At term delivery, RBC and plasma DHA had declined relative to 28 week DHA status in all mothers. The % TFA and concentration (p < 0.05) in maternal RBCs remained higher in the fish oil than placebo group (table 4).…”
Section: Fatty Acid Compositionmentioning
confidence: 84%
See 1 more Smart Citation
“…By 28 weeks, DHA accounted for a significantly higher % TFA in RBC (p < 0.05) and a higher concentration in both RBC and plasma (p < 0.05) in the fish oil compared with placebo group. At term delivery, RBC and plasma DHA had declined relative to 28 week DHA status in all mothers. The % TFA and concentration (p < 0.05) in maternal RBCs remained higher in the fish oil than placebo group (table 4).…”
Section: Fatty Acid Compositionmentioning
confidence: 84%
“…28 A supplemental maternal supply of DHA during gestation should increase maternal DHA status, and thereby increase the amount of DHA available to the fetus, thus enhancing postnatal DHA status of mother and infant. Moreover, an enhanced supply of DHA during the last trimester of pregnancy, when the visual and nervous systems are in a state of rapid growth and maturation, could enhance visual development.…”
mentioning
confidence: 99%
“…A potential adverse effect of hormonal contraception on erythrocyte fatty acid status has been observed by increasing some saturated fatty acids such as C16:0 and decreasing other unsaturated fatty acids such as EPA [17]. PUFA play an important role Polyunsaturated fatty acids in health and disease 275 in the brain and vascular development and in the normal course of pregnancy, as well as in a number of conditions as fetal growth retardation [18] and preeclampsia [19,20].…”
Section: Smoking Hormonal Contraception Pregnancy and Premenstrual mentioning
confidence: 99%
“…When PUFA status of smokers and non‐smokers has been compared, some studies found no difference (17, 18), while one study found lower long‐chain PUFA status in smoking than non‐smoking men (19). Further, neonates of smoking women had lower long‐chain PUFA status than neonates of non‐smoking women (9).…”
Section: Discussionmentioning
confidence: 99%